Profiling the acceleration and deceleration components in elite futsal players - Ribeiro, J. N.; Frazad, Y.; Illa, J.; Ferraz, A.; Nakamura, F.; Travassos, B. (International Journal of Performance Analysis in Sport, 2024)
This retrospective observational study explores the acceleration and deceleration demands of elite male futsal players (age: 28.8 ± 2.4 years, weight: 73.7 ± 6.2 kg, height: 175.9 ± 5.9 cm) in official matches. Utilising a local positioning system, tracking data from twelve matches involving two elite teams with nineteen players was analysed. Physical demands were assessed at various thresholds, considering standing and rolling efforts based on initial and final velocities. The most prevalent efforts were rolling accelerations (32.4%) and decelerations (31.3%), along with standing accelerations (18.7%) and decelerations (17.6%). A majority of efforts occurred within small distances (less than 10 metres), representing 27.9% to 71.1% of cases. Intensity comparisons revealed that larger distances consistently had significantly higher velocities (d = 0.67 to d = 5.91). High-intensity efforts over large distances were notably shorter than their low-intensity counterparts, both in standing (d = 1.75 to d = 1.98) and rolling (d = 0.64 to d = 0.82) effort types. In essence, elite futsal players predominantly engage in rolling accelerations and decelerations within short distances, exhibiting average speeds below 3 m·s-2. This insight into the nuanced dynamics of player movements provides valuable information for optimising training regimens and enhancing performance in elite futsal competitions.